2013
DOI: 10.1177/159101991301900213
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Extracranial Carotid Artery Stenting and Intracranial Aneurysm Coiling: Technical Feasibility and Clinical Outcome

Abstract: The coexistence of carotid artery stenosis and cerebral aneurysm in a patient presents challenges for treatment decision-making. The purpose of this study was to evaluate the technical feasibility and clinical outcome after single-stage extracranial carotid artery stenting (CAS) and ipsilateral intracranial aneurysm coiling in a single institution. From March 2005 to February 2011, 17 patients with 21 aneurysms underwent single-stage CAS and coiling for ipsilateral aneurysms. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Initial stenting facilitates subsequent reliable access to the intracranial aneurysm. Moreover, in this way, the risk of thromboembolic complications related to guiding catheter manipulation while passing through the stenosis decreases (17). Park et al (17) reported that initial placement of the stent was useful for decreasing the risk of embolic complications in their 17 patients treated with a single-stage endovascular method.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial stenting facilitates subsequent reliable access to the intracranial aneurysm. Moreover, in this way, the risk of thromboembolic complications related to guiding catheter manipulation while passing through the stenosis decreases (17). Park et al (17) reported that initial placement of the stent was useful for decreasing the risk of embolic complications in their 17 patients treated with a single-stage endovascular method.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this way, the risk of thromboembolic complications related to guiding catheter manipulation while passing through the stenosis decreases (17). Park et al (17) reported that initial placement of the stent was useful for decreasing the risk of embolic complications in their 17 patients treated with a single-stage endovascular method. In another study, Badruddin et al (18) performed CAS first, followed by treatment of the aneurysm in a single session successfully.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations